Pregnancy rates of day 4 and day 5 embryos after culture in an integrated time-lapse incubator - Verena Holschbach; Julia Weigert; Jens Erik Dietrich; Sabine Roesner; Markus Montag; Thomas Strowitzki; Bettina Toth (BMC, 2017)
Abstract Background The aim of this study was to compare pregnancy rates in patients undergoing IVF/ICSI with embryo transfer after 4 and 5 days of culture in a closed incubation system with integrated time-lapse imaging. Methods Out of n = 2207 in vitro fertilization (IVF)/ intracytoplasmic sperm injection (ICSI) cycles performed between January 2011 and April 2016 at a tertiary referral university hospital, a total of n = 599 IVF/ICSI cycles with prolonged embryo culture in an integrated time-lapse system (EmbryoScope© (Vitrolife)) until day 4 or 5 were retrospectively analyzed with regard to embryo morphology and pregnancy rates. Results A transfer on day 5 compared to a transfer on day 4 did not result in higher implantation and clinical pregnancy rates (IR 29.4% on day 4 versus 33.0% on day 5, p = 0.310; CPR 45.2% on day 4 versus 45.7% on day 5, p = 1.0). The percentage of ideal embryos transferred on day 4 was comparable to the rate of ideal embryos transferred on day 5 (41.6% versus 44.1%, p = 0.508). However, on day 4 a significantly higher number of embryos was transferred (1.92 on day 4 versus 1.84 on day 5, p = 0.023), which did not result in higher rates of multiple pregnancies. Conclusions Pregnancy rates in IVF/ICSI cycles with integrated time-lapse incubation and transfer on day 4 and 5 are comparable. This finding provides the clinician, IVF laboratory and patient with more flexibility. Trial registration This study was retrospectively registered by the local ethics committee of the University of Heidelberg on December 19, 2016 (registration number S-649/2016).